Kreativitas Mengajar Guru pada Masa Pandemi COVID-19 di Sekolah Alam Sriwijaya Palembang - Salsabil Zumrotul Auliya; Listya Listiningtyas; Lukmawati Lukmawati (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research discusses about Teacher’s Creative Teaching During Covid-19 Pandemic at Sriwijaya Nature School Palembang. This research uses qualitative method with descriptive design. The subject selection technique was using purposive sampling with criteria, aged 23-35 years, Muslim, permanent teacher status, teaching more than a year. Methods of data collection using interviews, observation, and documentation. In general, the results showed that the three subjects (MA, F, AY) had a high and unique picture of teaching creativity. Furthermore, the factors that influence Teacher’s Creative Teaching During Covid-19 Pandemic at Sriwijaya Nature School Palembang are the motivation to become a teacher, the feeling of being valued by students, the facilities available at the school, and self-potential related to teaching materials. In addition, social environmental factors such as the condition of students and relationships with colleagues also affect the Teacher’s Creative Teaching During Covid-19 Pandemic at Sriwijaya Nature School Palembang.